Affecting Factors of Generation and Weight Domestic Waste in Tanjung Karang Village Mataram City - Moh. Irvan; Astrini Widiyanti; Taufikul Hadi (Universitas Diponegoro, 2022)
Tanjung Karang Village is a priority tourism destination. Strategic tourist destinations need to maintain environmental cleanliness to achieve sustainable waste management to create comfort and satisfaction for visitors. The purpose of this study is to analyze the generation, weight, composition of waste, and influencing factors. The method in this study is a field survey to measure the generation and weight of waste with 13 households sample for 8 days. Data analysis has analyzed the Kolmogorov Smirnov Normality Test and the Dummy Variable Multiple Regression Test. The waste generation in Tanjung Karang Village is 3 liters/person/day and the weight of waste is 0.5 kg/person/day. The composition of the most waste is 56% organic waste. 28% plastic. and the others are metal, B3 waste, paper, glass, and so on. The most widely used plastic waste is food packaging plastic, High Density (HD), and High Density Polyethylene (HDPE). Influencing factors the generation and weight of waste are type of house, number of occupants, land area, occupation, and income. The recommendation for waste management in Tanjung Karang Village is that 56% of organic waste can be processed by composting, ecoenzyme, and biopore holes. Plastic waste 18% can be reduced by using plastic converted into containers.